C1q Deficiency and Neuropsychiatric Systemic Lupus Erythematosus - van Schaarenburg, Rosanne A.; Magro-Checa, César; Bakker, Jaap A.; Teng, Y. K. Onno; Bajema, Ingeborg M.; Huizinga, Tom W.; Steup-Beekman, Gerda M.; Trouw, Leendert A. (Frontiers in Immunology, 2016)
C1q deficiency is a rare immunodeficiency, which is strongly associated with the development of systemic lupus erythematosus (SLE). A mutation in one of the C1q genes can either lead to complete deficiency or to low C1q levels with C1q polypeptide in the form of low-molecular weight (LMW) C1q. Patients with C1q deficiency mainly present with cutaneous and renal involvement. Although less frequent, neuropsychiatric (NP) involvement has also been reported in 20% of the C1q-deficient patients. This involvement appears to be absent in other deficiencies of early components of the complement classical pathway (C1r/C1s, C2 or C4 deficiencies). We describe a new case with C1q deficiency with a homozygous G34R mutation in C1qC producing LMW-C1q presenting with a severe SLE flare with NP involvement. The serum of this patient contained very low levels of a LMW variant of C1q polypeptides. Cell lysates contained the three chains of C1q but no intact C1q was detected, consistent with the hypothesis of the existence of a LMW-C1q. Furthermore we provide a literature overview of NP-SLE in C1q deficiency and hypothesise about the potential role of C1q in the pathogenesis of NP involvement in these patients. The onset of NP-SLE in C1q deficient individuals is often more severe when compared with complement competent NP-SLE patients. An important number of cases present with seizures and the most frequent findings in neuroimaging are changes in basal ganglia and cerebral vasculitis. A defective classical pathway, because of non-functional C1q, does not protect against NP involvement in SLE. The absence of C1q and subsequently some of its biological functions may be associated with more severe NP-SLE.